Reformacija na Slovenskem: obravnava pri pouku slovenščine kot tujega jezika v Srbiji - Đukanović, Maja (Slavia Centralis, 2020)
Reformation in Slovenia: from the point of view of teaching Slovene as a foreign language in SerbiaThe article analyzes the method of presenting reformation and reformers in teaching Slovene as a foreign language in Serbia at four levels: (1) in the context of Slovene lessons at foreign universities, (2) in the teaching of Slovene in societies of Slovenes, (3) in commercial language courses, and (4) in the teaching of Slovene as an optional foreign language in elementary schools. The influence of values from the period of reformation to modern teaching of Slovene as a foreign language is presented in the context of knowledge of Slovene cultural history and the formation of Slovene national identity. In the modern process of teaching foreign languages, a great emphasis is placed on accepting diversity and multiculturalism, which also applies to teaching Slovene. Courses encompassing literature from the period of Slovene Reformation and the Slovene Reformation in general, therefore in the context of teaching Slovene as a second or foreign language, contribute also to the development of intercultural dialogue and also develop multicultural competences. The analyzed material was taken from textbooks and manuals of the Center for Slovene as a Second and Foreign Language of the Faculty of Arts of the University of Ljubljana.
Keywords: teaching Slovene as a foreign language; reformation; reformers; Protestantism; teaching Slovene